Could knee joint mechanics during the golf swing be contributing to chronic knee injuries in professional golfers? - Carson, H.; Richards, J.; Coleman, S. G. S. (Journal of Sports Sciences, 2020)
Full three-dimensional movements and external moments in golfers` knees and the possible involvement in injuries have not been evaluated using motion capture at high sample frequencies. This study measured joint angles and external moments around the three anatomical axes in both knees of 10 professional golfers performing golf drives whilst standing on two force plates in a motion capture laboratory. Significant differences were found in the knee joint moments between the lead and trail limbs for the peak values and throughout all stages during the swing phase. A significantly higher net abduction moment impulse was seen in the trail limb compared with the lead limb (-0.518 vs. -0.135 Nms/kg), indicating greater loading over the whole swing, which could contribute to knee lateral compartment or anterior cruciate ligament injuries. A significant correlation (r = -0.85) between clubhead speed at ball contact and maximum joint moment was found, with the largest correlations being found for joint moments at the top of the backswing event and at the end of the follow-through. Therefore, although knee moments can contribute to high clubhead speeds, the large moments and impulses suggest that they may also contribute to chronic knee injuries or exacerbate existing conditions.